THE EMERGENCE OF THE PERIPHERY IN THE WORLD SYSTEM: FROM THE BANDUNG CONFERENCE TO THE BUENOS AIRES CONFERENCE (1955-1978) - Danilevicz Pereira, Analúcia; Medeiros, Klei (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This article aims to analyze the initial stage of development of South-South relations and the emergence of the periphery, taking into account that South-South Cooperation, as known today, gave its first steps in the context of the Cold War, with the decolonization of Afro-Asiatic countries and the formation of the first arrangements connecting the global periphery, such as the Bandung Conference and the creation of the Non-Aligned Movement, the G-77 and of the UNCTAD. In this initial phase, the goal was to guarantee decolonization and non-alignment. Since the decade of 1970, countries from Latin America and Sub-Saharan Africa began to be increasingly involved with the agenda of the Third World, in an attempt to foment political, economic and technical cooperation among developing countries. South-South Cooperation became progressively institutionalized within the UN, in particular due to the Buenos Aires Conference in 1978.